Shifting Paradigms of Sexual Violence Victims within the Integrated Criminal Justice System in Indonesia - Josephine Suprapto; Made Aditya Pramana Putra (International Journal of Business, Law, and Education, 2026)
This article examines the transformation of victim protection in Indonesia's integrated criminal justice system following the enactment of Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS). It asks whether the statutory shift toward a victim-centered approach has been translated into adjudicative practice, particularly in relation to restitution and psychological rehabilitation. The study applies normative or doctrinal legal research. It combines statutory, historical, conceptual, and case approaches, with particular attention to Denpasar District Court Decision No. 77/Pid.Sus/2026/PN Dps. Primary legal materials include Law No. 12 of 2022, Law No. 31 of 2014 on Witness and Victim Protection, Law No. 1 of 2023 on the Criminal Code, and Supreme Court Regulation No. 3 of 2017. The analysis is guided by Lawrence M. Friedman's legal system theory and Nonet and Selznick's responsive law theory. The article finds a significant gap between progressive statutory substance and courtroom implementation. Although the UU TPKS recognizes victims' rights to care, protection, recovery, restitution, and rehabilitation, judicial practice remains substantially offender-oriented. In the case studied, the decision successfully imposed criminal punishment but did not integrate restitution or victim recovery into the operative part of the judgment. The problem is not merely doctrinal but systemic: legal substance has advanced faster than legal structure and legal culture. The article contributes to Indonesian criminal justice scholarship by identifying a procedural vacuum in the enforcement of victim recovery rights. It argues for mandatory restitution calculation, judicial authority to address recovery ex officio, and institutional synchronization among investigators, prosecutors, judges, LPSK, social services, and victim assistance providers.